Temporal Variation and Source Analysis of Atmospheric CH4 at Different Altitudes in the Background Area of Yangtze River Delta - Meng Shan; Honghui Xu; Lujie Han; Yuting Pang; Juncheng Ma; Chao Zhang (Atmosphere, 2022)
Through an analysis of CH4 data observed at different altitudes at the atmospheric background station in Lin’an from 2016 to 2020, in combination with back-trajectory and distribution characteristics of potential source areas, the CH4 concentration variations at higher and lower altitudes and their relationships with sources and sinks were studied. The results showed that the CH4 concentration was characterized by notable diurnal variations. The largest concentration difference occurred between 5 and 7 a.m.; the concentration difference in summer was higher than that in the other three seasons. Background filtering of the hourly CH4 concentration was carried out using a numerical method. The results showed that the difference in the CH4 background concentration between the two altitudes was 4.6 ppb (SD = 7.9). The CH4 background concentrations at the two altitudes had the same seasonal variation: double peaks and valleys. The peaks appeared in May and December, and the valleys appeared in March and July. In spring and summer, the potential CH4 source areas were mainly distributed in the rice planting and wetland discharge regions. In autumn, they were mainly distributed in regions affected by fugitive emissions from rice planting and coal mining. In winter, they were mainly distributed in livestock and poultry management regions.